Contrast loading: power output and rest interval effects on neuromuscular performance - Sotiropoulos, K.; Smilios, I.; Douda, H. T.; Christou, M.; Tokmakidis, S. P. (International Journal of Sports Physiology and Performance, 2014)
Purpose: This study examined the effect of rest interval after the execution of a jump-squat set with varied external mechanical-power outputs on repeated-jump (RJ) height, mechanical power, and electromyographic (EMG) activity. Methods: Twelve male volleyball players executed 6 RJs before and 1, 3, 5, 7, and 10 min after the execution of 6 repetitions of jump squats with a load: maximized mechanical-power output (Pmax), 70% of Pmax, 130% of Pmax, and control, without extra load. Results: RJ height did not change (P = .44) after the jump squats, mechanical power was higher (P = .02) 5 min after the 130%Pmax protocol, and EMG activity was higher (P = .001) after all exercise protocols compared with control. Irrespective of the time point, however, when the highest RJ set for each individual was analyzed, height, mechanical power, and EMG activity were higher (P = .001-.04) after all loading protocols compared with control, with no differences observed (P = .53-.72) among loads. Conclusions: Rest duration for a contrast-training session should be individually determined regardless of the load and mechanical-power output used to activate the neuromuscular system. The load that maximizes external mechanical-power output compared with a heavier or a lighter load, using the jump-squat exercise, is not more effective for increasing jumping performance afterward.